2007
DOI: 10.1002/jnr.21239
|View full text |Cite
|
Sign up to set email alerts
|

β‐amyloid precursor protein can be transported independent of any sorting signal to the axonal and dendritic compartment

Abstract: In neurons, amyloid precursor protein (APP) is localized to the dendritic and axonal compartment. Changes in subcellular localization affect secretase cleavage of APP, altering the generation of Abeta, and presumably also its pathogenic features. It was reported that APP is sorted initially to the axon and transcytosed subsequently to the somatodendritic compartment. This may be carried out by a recessive dendritic sorting signal in the cytoplasmic C-terminus, possibly the tyrosine based basolateral sorting si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 60 publications
2
33
1
Order By: Relevance
“…Along this line, APP lacking the cytoplasmic domain (DC) (where the basolateral sorting signal is located; see above) is transported along neurites with characteristics indistinguishable from wild-type APP ( Fig. 7a; Back et al 2007;Szodorai et al 2009). Therefore, the basolateral sorting signal in the carboxy-terminal region of APP documented in MDCK studies seems to have no function for polarized sorting in neurons.…”
Section: Trafficking Of App In Neuronsmentioning
confidence: 98%
See 1 more Smart Citation
“…Along this line, APP lacking the cytoplasmic domain (DC) (where the basolateral sorting signal is located; see above) is transported along neurites with characteristics indistinguishable from wild-type APP ( Fig. 7a; Back et al 2007;Szodorai et al 2009). Therefore, the basolateral sorting signal in the carboxy-terminal region of APP documented in MDCK studies seems to have no function for polarized sorting in neurons.…”
Section: Trafficking Of App In Neuronsmentioning
confidence: 98%
“…An axonal sorting signal was mapped to a juxtamembrane domain which includes the Ab-domain ; however, a recent report showed that APP is transported into axons and dendrites without apparent sorting signals (Back et al 2007). Along this line, APP lacking the cytoplasmic domain (DC) (where the basolateral sorting signal is located; see above) is transported along neurites with characteristics indistinguishable from wild-type APP ( Fig.…”
Section: Trafficking Of App In Neuronsmentioning
confidence: 99%
“…Two peptide sequences in the tail of APP that are important for its basolateral sorting have been identified in polarized Madin Darby canine kidney cells (a renal cell type) (De Strooper et al, 1995b;Haass et al, 1995). Apparently, axonal transport of APP in polarized neurons does not require these basolateral sorting signals, because APP mutants that lack the entire cytoplasmic tail are still sorted normally along axons and dendrites (Back et al, 2007).…”
Section: Cellular Trafficking Of App Controls Processing Fatesmentioning
confidence: 99%
“…It has recently been reported that under steady-state conditions APP is sorted equally to the axonal and somatodendritic compartment in primary neurons (Back et al, 2007). We examined the distribution pattern of endogenous APP and the trafficking of APP-GFP in primary cultured cortical neurons.…”
Section: App Is Trafficked To Both Presynaptic and Postsynaptic Compamentioning
confidence: 99%